Programa de intervención por entrenamiento en habilidades sociales en el manejo de emociones, con los docentes de la Escuela de Educación Básica Ruperto Alarcón Falconí de la parroquia de Cotogchoa, en un rango de edad de 25 a 60 años, durante el periodo marzo 2017 – septiembre 2017 - Coral Florez, Melissa (2017)
The work of systematization of the experience about the execution of the project: intervention program for training in social skills in the management of emotions, with the teachers of the Basic School of Education Ruperto Alarcón Falconí of the parish of Cotogchoa, in a range of age from 25 to 60 years, during the period March 2017 to September 2017, aims to reconstruct the experience to identify errors, successes, difficulties and the different factors that intervened during the process of learning social skills in the management of emotions with the teachers The actions carried out during the sessions of the intervention program were taken as a systematization axis, using different techniques from the theoretical cognitive-behavioral line for training in social skills. The purpose of the systematization are the activities developed by the author in the sessions. The methodology describes the tools used to reconstruct the experience. There are 3 key questions. In the processing of information, an analysis matrix is made, allowing a structure to be given to the activities carried out during the training. The first part ends the perspectives from which the information collected will be analyzed. In the second part, the justification of the execution of the project is realized, later a characterization of the beneficiaries is made. The interpretation is made from two approaches, qualitative and quantitative. It also describes the main learning that left the author experience. Finally, conclusions, recommendations, bibliographical references and annexes.